Civilian relations between Norman Sicily and the Islamic Maghreb during the 5th century - 6Th Century / 11-12 AD - Laid Bakri; Mefteh Khelfat (Social Empowerment Journal, 2021)
Through this paper, we seek to address the issue of cultural communication between Sicily and the inhabitants of the Maghreb from 5-6 Ah / 11-12 AD in the time of the Normans' entry into Sicily, their kingdom, their conquest of the African coast, and some of its regions which were governed by them and the resulting of cultural and cultural links and contacts, reflecting one of the positive interactions between the two peoples The geographical unity and turmoil of Sicily's political situation, and what the Normans were known to take advantage of the culture of the other in strengthening it, and then highlighting the influences in the cultural field, including the  different fields of science. The activity during the journeys of scientists and writers had an impact on their activation and in the field of civilization, including the urban nature and systems of governance, going beyond the prevailing vision that portrayed the Normans (Vikings) just a group of pirates whose lives are based on the use of raids and cruelty And ignoring the factors that have refined their complex abilities and values and their contribution, especially in this field.